Strategi Media Bamusi TV dalam Meningkatkan Reputasi Digital - Desi Lestari (CV. ITTC INDONESIA, 2023)
Digital reputation is currently a person's assessment of agencies or organizations that influence the general public. Digital reputation needs to be paid close attention, so that there are no digital footprints that can tarnish the good name of the institution or organization. Thus, digital reputation management must be improved in order to be able to provide a positive outlook for the general public. Thus, Bamusi formed Instagram and YouTube media Bamusi TV as a means of spreading da'wah in order to be able to enhance the digital reputation of the Baitul Muslimin Indonesia (Bamusi) organization. This study uses a qualitative descriptive method to describe the data sources that have been found with the help of data collection techniques in the form of literature studies, interviews, and documentation in order to strengthen the data sources that have been found by researchers. The results of this study indicate that the Baitul Muslimin Indonesia (Bamusi) organization formed social media with the name Bamusi TV so that it can easily disseminate information about Bamusi's religious and social agenda, so as to increase digital credibility or reputation for Bamusi. In increasing digital reputation, Bamusi TV has a da'wah strategy that is implemented to support digital reputation through managing Bamusi TV's social media.